PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DI PERUSAHAAN PERTAMBANGAN BAHAN GALIAN C (STUDI PADA PT. ALAM BARU JAYA GIANYAR) - I Putu Ngurah Aldeva Wijaya Putra; Komang Satria Wibawa Putra (CV. Lafadz Jaya, 2026)
In the laws and regulations of the Republic of Indonesia, there are several regulations that have regulated the obligation to use the CSR concept. The purpose of the study was to determine the Implementation of Corporate Social Responsibility (CSR). The empirical legal research method with a factual approach to field data collected through primary and secondary data types, both through interviews and literature studies, was analyzed descriptively (Descriptive analysis). The results of the analysis showed that the Implementation of the Corporate Social Responsibility program of PT. Alam Baru Jaya can be said to be less than optimal. This is indicated by the low realization of Corporate Social Responsibility which only carries out English language education activities, capital assistance through cooperation with cooperatives and seed assistance. obstacles and barriers both from within the Company and also from outside the Company. From within the Company, among others, limited human resources, limited financial resources/budget, while obstacles from external organizations, namely from the community or the company environment.